WE ARE ALL GODâ€™S CREATION: FREE TAKJIL ACTION AS PART OF RELIGIOUS MODERATION - Heydemans, Nency Aprilia; Andalangi, Jammer Prayerson; Nainggolan, Alon Mandimpu; Kasiahe, Octaniel Michael; Lahamendu, Natalia Olivia Kusuma Dewi (Al-Qalam, 2023)
This article explores the significance of â€œTorang samua ciptaan Tuhanâ€ (We are All Godâ€™s Creation) within the Tateli Minahasa community. It focuses on sharing free iftar meals organized by students from the Sociology of Religion Study Program at Institut Agama Kristen Negeri Manado (Manado State Christian Institute). This event showcased the students' compassionate nature as they cared for and cared for others, particularly those from diverse religious backgrounds. This action demonstrates the harmonious coexistence of Christian lecturers and students from diverse ethnic backgrounds with the Muslim community in Tateli. The study employed a phenomenological approach, utilizing observations and interviews to examine the impact of helping others as a tangible act of love on developing a friendly and tolerant religious environment in Indonesia. The findings of thestudy suggest that the paradigm â€œTorang samua ciptaan Tuhanâ€ has the potential to enhance the sense of brotherhood and foster closeness, tolerance, and cooperation in diverse settings.